The Investigation of Request Strategies By EFL Learners of The International Institute of Tourism and Business Denpasar - Wahyu, Gede Eka; Evi Wahyu Citrawati, Ni Putu (Humanis, 2021)
Communicative competence has been the goal teaching of a second or foreign language. In acquiring the language, speakers of language also acquire the rules of knowledge and choose the speech acts when communicating with others. This study aimed to investigate the act of request strategies and request perspectives produced by the student of The International Institute of Tourism and Business Denpasar. There are fifty students’ involved in the study with intermediate level in their English proficiency. The data is collected with a written Discourse Completion Test (DCT) which has ten request situations. Soshana Blum Kulka and Olshtain’s (1984) theory is used to categorize the speech acts produce in analyzing data. The result of the project showed that most of the students use internal modification and the number of students external modification in their speech acts.